2020
DOI: 10.1007/s13197-020-04420-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in chemical and anti-nutritional properties of pasta enriched with raw and germinated quinoa (Chenopodium quinoa Willd.) flours

Abstract: In this study, quinoa seeds were processed to flour in ungerminated (raw) and germinated forms. Raw quinoa flour (RQF) and germinated quinoa flour (GQF) were replaced (0, 10, 20 and 30%) with wheat semolina in pasta formulation to improve nutritional and functional properties of pasta. Some chemical (ash, crude fat, crude protein, total phenolic content (TPC), antioxidant activity (AA) and mineral matter), anti-nutritional (phytic acid), physical and sensory properties of pasta samples were determined. With ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 24 publications
5
23
1
1
Order By: Relevance
“…There was a 45.20 and 26.71% increase in iron and zinc content, respectively after the germination process. The results are comparable to the study carried out by Demir and Bilgiçli (2020) who reported an increase of 16.92% and 55.60% in iron and zinc content respectively during the germination of quinoa grains for 72 h. The values for Mn content increased from 14.30 (raw grain) to 16.2 mg/kg (G72) after the soaking and there was a 13.29% increase in manganese content after the germination process.…”
Section: Effect Of Soaking and Germination On Nutritional And Anti-nutritional Componentssupporting
confidence: 85%
See 1 more Smart Citation
“…There was a 45.20 and 26.71% increase in iron and zinc content, respectively after the germination process. The results are comparable to the study carried out by Demir and Bilgiçli (2020) who reported an increase of 16.92% and 55.60% in iron and zinc content respectively during the germination of quinoa grains for 72 h. The values for Mn content increased from 14.30 (raw grain) to 16.2 mg/kg (G72) after the soaking and there was a 13.29% increase in manganese content after the germination process.…”
Section: Effect Of Soaking and Germination On Nutritional And Anti-nutritional Componentssupporting
confidence: 85%
“…Similarly, the phytic acid contents reduced significantly (p ≤ 0.05) from 1.03% (RG) to 0.54% (G72). There was a 47.57% decrease in phytic acid content during the germination process of 72 h. Demir and Bilgiçli (2020) observed a similar decrease in phytic content (77.23%) during germination of grains for 72 h.…”
Section: Effect Of Soaking and Germination On Nutritional And Anti-nutritional Componentssupporting
confidence: 63%
“…The use of 20-30% raw or germinated quinoa in GF pasta formulation caused a significant (p < 0.05) decrease in the appearance score. In a similar study, Demir and Bilgic¸li (2020) stated that the use of increasing QF in regular pasta formulation decreased the overall acceptability and appearance scores. Although high usage rates of raw or germinated quinoa (20-30%) caused a decrease in overall acceptability scores, all the scores obtained were above 5 and were acceptable for general appreciation.…”
Section: Evaluation Of Sensory Features Of Gf Pasta Samplesmentioning
confidence: 91%
“…However, increasing the overall acceptability score of the MP could be due to the desired taste and texture of this sample. Despite these results, a reduction in the desirability of pasta sensory scores has been reported by the addition of similar ingredients such as soy flour (Shogren et al., 2006 ) and quinoa flour (Demir & Bilgiçli, 2020 ). Also, La Gatta et al., ( 2017 ) suggested that the fortification of pasta with high‐fiber ingredients may cause a dilution of the gluten‐protein matrix and result in an adverse effect on its sensory feature.…”
Section: Resultsmentioning
confidence: 99%